2020
DOI: 10.21577/0100-4042.20170509
|View full text |Cite
|
Sign up to set email alerts
|

Emissões De Poluentes Atmosféricos Em Condições Reais De Pavimentação Asfáltica: Material Particulado, Black Carbon E Hidrocarbonetos Policíclicos Aromáticos

Abstract: Intensive use of asphalt generates pollutants into the atmosphere which are harmful to the environment and worrying for occupational health. The application of asphalt products leads to emissions of significant concentrations of polycyclic aromatic hydrocarbons (PAHs) and particulate matter (PM) to the atmosphere. This paper aims to assess the pollutant emissions into the atmosphere in real conditions of asphalt paving through sampling and quantification of PM, Black Carbon (BC) and PAHs in fine particulate fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
(31 reference statements)
0
2
0
3
Order By: Relevance
“…As amostragens iniciaram após a remoção do asfalto antigo e durante os três primeiros dias de coleta houve a aplicação da nova massa asfáltica. A partir do quarto dia, já havia tráfego de ônibus no local (Piracelli et al, 2020).…”
Section: Locais De Amostragemunclassified
See 1 more Smart Citation
“…As amostragens iniciaram após a remoção do asfalto antigo e durante os três primeiros dias de coleta houve a aplicação da nova massa asfáltica. A partir do quarto dia, já havia tráfego de ônibus no local (Piracelli et al, 2020).…”
Section: Locais De Amostragemunclassified
“…A partir das concentrações de MP2,5 e BC ao longo dos últimos 8 anos, é apresentada a tabela 5 para a comparação dos dados. Considerando as recomendações da OMS para o limite diário de MP2,5 de 15 µg m -3 , todas as concentrações médias, com exceção da obtida por Piracelli et al (2020), estão acima do nível recomendado. Em um estudo em que as amostragens ocorreram entre maio de 2017 e julho de 2018 (SANTOS et al, 2020) em Londrina, a concentração média de MP2,5 foi de 35,4 µg m -3 sendo possível observar diminuição expressiva da concentração média de MP2,5 em comparação com a realizada em abril de 2020.…”
Section: Fonte:lemos(2015)unclassified
“…Segundo Balbo (2015), cada camada do pavimento possui uma ou mais funções específicas que devem proporcionar aos veículos as condições adequadas de suporte e rolamento em qualquer condição climática. Dessa forma, a pavimentação asfáltica é a principal forma de revestimento de vias de rodagem (Piracelli, 2020).…”
Section: Pavimentação Asfálticaunclassified
“…7,8 Research has identified significantly heightened levels of VOCs, such as benzene, toluene, ethylbenzene, and xylene, in the vicinity of asphalt mixing plants, storage tanks, and paving sites compared to background ambient conditions. 9,10 Subsequently released into the atmosphere, VOCs engage in photochemical reactions that produce ozone, fine particulate matter, and secondary organic aerosol (SOA), which degrade regional air quality and contribute to climate change. 11 Consequently, VOC emissions from asphalt materials have posed substantial threats to both the atmospheric environment and human health.…”
Section: Introductionmentioning
confidence: 99%
“…However, mounting concerns have emerged regarding the potential effects of asphalt materials on air quality and human health during high-temperature mixing, transportation, and paving processes. , Asphalt binders are derived from the distillation and fractionation of crude oils, resulting in a complex mixture of thousands of hydrocarbon components . When heated to temperatures of 140–180 °C, necessary for fluidity during construction operations, volatile organic compounds (VOCs) can volatilize from hot asphalt into the atmosphere. , Research has identified significantly heightened levels of VOCs, such as benzene, toluene, ethylbenzene, and xylene, in the vicinity of asphalt mixing plants, storage tanks, and paving sites compared to background ambient conditions. , Subsequently released into the atmosphere, VOCs engage in photochemical reactions that produce ozone, fine particulate matter, and secondary organic aerosol (SOA), which degrade regional air quality and contribute to climate change . Consequently, VOC emissions from asphalt materials have posed substantial threats to both the atmospheric environment and human health.…”
Section: Introductionmentioning
confidence: 99%